1984
DOI: 10.1021/om00087a007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermodynamics of the reversible reaction between carbon monoxide and palladium(I) dimers containing bis(diphenylphosphino)methane

Abstract: The kinetic and thermodynamic parameters for the reversible insertion of carbon monoxide into the palladium-palladium bond of Pd2(dpm)2X2 complexes (dpm = Ph2PCH2PPh2; X = Cl, Br, I, NCO) in iVJV-dimethylacetamide solution have been determined by spectrophotometric methods. The forward reaction is first order in both Pd2 and CO and occurs on the stopped-flow time scale at around ambient temperatures, the rate constants being similar for the four systems (3.15-6.60) X 103 M"1 11s-1 at 24 °C. The equilibrium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Reaction [I] is readily monitored by solution electronic spectroscopy; species such as 1 are reddish-orange with two to three absorption maxima in the 340-590 nm region (2,15,16), while the p-S products (2) are brown and have absorption maxima in the 325-350 and 470-485 nm regions (2,17). Figure 3 shows spectral changes on treating a CH2C12 solution of the bromide l b with H2S at 25°C; rates for the bromide system were followed by observing the decreasing absorption at 428 nm as a function of time, and the observed isosbestic point showed a well-behaved system.…”
Section: Kinetic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction [I] is readily monitored by solution electronic spectroscopy; species such as 1 are reddish-orange with two to three absorption maxima in the 340-590 nm region (2,15,16), while the p-S products (2) are brown and have absorption maxima in the 325-350 and 470-485 nm regions (2,17). Figure 3 shows spectral changes on treating a CH2C12 solution of the bromide l b with H2S at 25°C; rates for the bromide system were followed by observing the decreasing absorption at 428 nm as a function of time, and the observed isosbestic point showed a well-behaved system.…”
Section: Kinetic Datamentioning
confidence: 99%
“…Within 1, the Pd-Pd bond strength is expected to increase in the order I < Br < C1 (16), the reverse of the trans effect of the halides (32), and thus the reactivity trend is not dominated by differences in the metal-metal bond strength. Reactivity of 1 toward CO is also C1> Br > I in terms of equilibrium constants, and this is governed by the rate of CO loss from the p-carbonyl product that decreases in the reverse order (I > Br > Cl), the forward carbonylation reaction rates being essentially the same for the three halide species (15); it has been suggested that the strength of the metal-carbonyl bond in the product (I < Br < C1) governs the reactivity trend (15). Such could be the case in I the H2S systems, if the k-' step of the mechanism outlined in eq.…”
Section: Using V(s-h)mentioning
confidence: 99%
“…24,25 This is in line with previously reported experimental bond energy data of a related Pd(I) dimer, determined to be between 21 and 29 kcal mol À1 . 26 For the alternative dinuclear pathway we were able to locate three distinctly different transition states for halide exchange at iodobenzene (see Fig. 2), featuring (i) direct oxidative addition by Pd-Pd (TS A ), in which the coordination number at Pd is Scheme 3 Attempted reductive elimination from Pd(II).…”
mentioning
confidence: 99%
“…By contrast, odd oxidation state palladium is comparatively scarce in catalysis. Due to their unpaired electrons and the potential formation of a rather strong Pd−Pd bond (usually about 25 kcal mol −1 ) [2] these oxidation states tend to form dinuclear complexes. A wide variety of Pd I dimers has been synthesized and has been known for decades.…”
Section: Introductionmentioning
confidence: 99%